MEMBANGUN EKOSISTEM PELAYANAN YANG SEHAT: PERAN KEPEMIMPINAN TRANSFORMATIF DALAM MEMITIGASI RISIKO MENTAL HEALTH PELAYAN TUHAN DI ERA DIGITAL - Kaharudin, Erlitawati; Lim, Suleman (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2026)
This study is motivated by the challenges faced by ministers of God who are increasingly vulnerable to multidimensional pressures in line with the advancement of digital technology, including constant public exposure, instant criticism, and the massive flow of information. These developments have the potential to trigger mental health disturbances among ministers. The research employs a literature review method. The objective of this study is to explore the role of transformational leadership in mitigating the mental health challenges of ministers in the digital era. The findings reveal that transformational leadership in mental health mitigation involves the integration of various approaches, including the reorientation of leadership paradigms, the strengthening of positive interpersonal relationships, the catalysis of motivation and problem-solving, the empowerment of digital literacy and ethics, and the integration of spirituality as essential steps toward fostering mental health within a healthy ministry ecosystem.